A multiple technology-based and individually-tailored Sit Less program for people with cardiovascular disease: A randomized controlled trial study protocol. - Chorong Park; Britta Larsen; Mulubrhan Mogos; James Muchira; Mary Dietrich; Marianna LaNoue; Jason Jean; John Norfleet; Abigail Doyle; Soojung Ahn; Shelagh Mulvaney (PLoS ONE)
Sedentary behavior, a key modifiable risk factor for cardiovascular disease, is prevalent among cardiovascular disease patients. However, few interventions target sedentary behavior in this group. This paper describes the protocol of a parallel two-group randomized controlled trial for a novel multi-technology sedentary behavior reduction intervention for cardiovascular disease patients (registered at Clinicaltrial.gov, NCT05534256). The pilot trial (n = 70) will test a 12-week "Sit Less" program, based on Habit Formation theory. The 35 participants in the intervention group will receive an instructional goal-setting session, a Fitbit for movement prompts, a smart water bottle (HidrateSpark) to promote hydration and encourage restroom breaks, and weekly personalized text messages. A control group of 35 will receive the American Heart Association's "Answers by Heart" fact sheets. This trial will assess the feasibility and acceptability of implementing the "Sit Less" program with cardiovascular disease patients and the program's primary efficacy in changing sedentary behavior, measured by the activPAL activity tracker. Secondary outcomes include physical activity levels, cardiometabolic biomarkers, and patient-centered outcomes (i.e. sedentary behavior self-efficacy, habit strength, and fear of movement). This study leverages commonly used mobile and wearable technologies to address sedentary behavior in cardiovascular disease patients, a high-risk group. Its findings on the feasibility, acceptability and primary efficacy of the intervention hold promise for broad dissemination.